0554 Insomnia Disorder Predicts Stressful Life Events in Individuals Who Have Recently Experienced Involuntary Job Loss. (27th May 2020) - Skobic, I; Howe, G; Haynes, P L
Abstract: Introduction: The stress generation hypothesis posits that depressed (versus non-depressed) individuals generate more stressful life events, especially events for which they are at least partly responsible (i.e., dependent events). Insomnia disorder interferes with emotion regulation, potentially leading to impaired decision-making and increased stress generation. We hypothesized that insomnia disorder would lead to an increased number of stressful life events in our sample of adults who have recently experienced involuntary job loss. Methods: Assessing Daily Activity Patterns through Occupational Transitions is a longitudinal study examining linkages between job-loss, sleep, obesity, and mental health. We used baseline and 3-month follow-up data from 137 participants who completed the Life Events and Difficulties Schedule, a contextual life event measure. Insomnia disorder was coded yes if participants met ICSD-3 criteria for a current chronic or acute insomnia disorder on the Duke Structured Interview for Sleep Disorders. Covariates included age, gender, and race. Linear and logistic regression were employed to assess changes in number of events over time. Secondary analysis examined the relationship between insomnia and dependent stressful life events specifically. Results: When controlling for covariates, insomnia disorder at study baseline predicted the number of stressful life events generated between baseline and 3-month follow-up (β =.60, se=.30, t=1.99, p=.05). Conversely, events at baseline did not predict insomnia disorder at follow-up when controlling for baseline insomnia disorder (OR=.98, CI=.82-1.17). Secondary analysis revealed a trend toward increased generation of dependent events among individuals with insomnia disorder (β =.37, se=.23, t = 1.6, p=.11). Conclusion: Our analyses provide preliminary evidence for a causal relationship between insomnia disorder and stress generation. Additional research is needed to replicate and examine the mechanisms behind this relationship. This extension of the stress generation hypothesis may have important implications for harm reduction interventions for insomnia disorder. Support: #1R01HL117995-01A1.